Improving the Substrate Affinity and Catalytic Efficiency of β-Glucosidase Bgl3A from Talaromyces leycettanus JCM12802 by Rational Design - Wei Xia; Yingguo Bai; Pengjun Shi (Biomolecules, 2021)
Improving the substrate affinity and catalytic efficiency of β-glucosidase is necessary for better performance in the enzymatic saccharification of cellulosic biomass because of its ability to prevent cellobiose inhibition on cellulases. Bgl3A from Talaromyces leycettanus JCM12802, identified in our previous work, was considered a suitable candidate enzyme for efficient cellulose saccharification with higher catalytic efficiency on the natural substrate cellobiose compared with other β-glucosidase but showed insufficient substrate affinity. In this work, hydrophobic stacking interaction and hydrogen-bonding networks in the active center of Bgl3A were analyzed and rationally designed to strengthen substrate binding. Three vital residues, Met36, Phe66, and Glu168, which were supposed to influence substrate binding by stabilizing adjacent binding site, were chosen for mutagenesis. The results indicated that strengthening the hydrophobic interaction between stacking aromatic residue and the substrate, and stabilizing the hydrogen-bonding networks in the binding pocket could contribute to the stabilized substrate combination. Four dominant mutants, M36E, M36N, F66Y, and E168Q with significantly lower Km values and 1.4–2.3-fold catalytic efficiencies, were obtained. These findings may provide a valuable reference for the design of other β-glucosidases and even glycoside hydrolases.